Results of the International scientific conference «A heritage of the people of Central Asia and adjacent territories: research, preservation and use» (September 9-10, 2009, Kyzyl) - Opey-ool, Ulyana P. (The New Research of Tuva, 2009)
Results of the International scientific conference «A heritage of the people of Central Asia and adjacent territories: research, preservation and use» (September 9-10, 2009, Kyzyl)
Keywords: conference; Museum; Tuva; international; Central Asia; review